Forces exerted during microneurosurgery: a cadaver study. Issue 2 (16th January 2014) - Marcus, Hani J.; Zareinia, Kourosh; Gan, Liu Shi; Yang, Fang Wei; Lama, Sanju; Yang, Guang‐Zhong; Sutherland, Garnette R.
Abstract Background A prerequisite for the successful design and use of robots in neurosurgery is knowledge of the forces exerted by surgeons during neurosurgical procedures. The aim of the present cadaver study was to measure the surgical instrument forces exerted during microneurosurgery. Methods An experimental apparatus was set up consisting of a platform for human cadaver brains, a Leica microscope to provide illumination and magnification, and a Quanser 6 Degrees‐Of‐Freedom Telepresence System for tissue manipulation and force measurements. Results The measured forces varied significantly depending on the region of the brain (P = 0.016) and the maneuver performed (P < 0.0001). Moreover, blunt arachnoid dissection was associated with greater force exertion than sharp dissection (0.22 N vs. 0.03 N; P = 0.001). Conclusions The forces necessary to manipulate brain tissue were surprisingly low and varied depending on the anatomical structure being manipulated, and the maneuver performed. Knowledge of such forces could well increase the safety of microsurgery. Copyright © 2014 John Wiley & Sons, Ltd.